Integrasi Sains dan Agama Berbasis Moderasi Beragama di Pondok Pesantren Sains Salman Assalam Cirebon - Saumantri, Theguh; Hamdani, Hamdan; Abdullah Romdon, Mujib (CV Kalimasada Group, 2023)
The Islamic Boarding School is a special educational institution that focuses on religious learning. At first, the Islamic Boarding School used the Turats book as a reference in teaching morality to the studens. However, at the Salman Assalam Islamic Boarding School, there are visible developments in religious and scientific education, especially in the field of science and technology. This study aims to examine the integration of science and religion based on religious moderation at the Salman Assalam Islamic Boarding School in Cirebon. The methodology used is a qualitative method through library research, which includes field studies with observations, documentation, and interviews. The results showed that the Salman Assalam Cirebon Science Islamic Boarding School applied an integrated science and religion approach based on religious moderation with various strategies. The learning process in this Islamic Boarding School combines scientific knowledge with religious values in order to create a holistic understanding of the world and life. The implementation of religious moderation values instilled is the formation of morals. The values of religious moderation are actualized in cognitive, affective, and practical aspects.